2013
DOI: 10.4236/ojcd.2013.33014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic findings of alstrom syndrome with a case report

Abstract: Alstrom Syndrome is an autosomal recessive genetic disorder affecting multiple systems. The characteristic features of this syndrome are obesity, type 2 diabetes mellitus, rod-cone dystrophy, hearing loss. Developmental delay, nistagmus, dilated cardiomyopathy, hypertension, recurrent pulmonary infections, short stature, hepatic and renal failure endocrine abnormalities are other clinical features of this syndrome. Here we report on a case with Alström Syndrome at the age of thirteen. He was referred to medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…As mentioned above Alstrom Syndrome is an autosomal recessive, single gene disorder (ALMS1-2p13) presenting with childhood obesity, hyperinsulinemia, type 2 diabetes mellitus, progressive cone-rod dystrophy leading to blindness, sensorineural hearing loss and function loss of multiple organs [4]. In present case report child had loss of vision, obesity, T2DM and hearing impairment from the first year of life.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As mentioned above Alstrom Syndrome is an autosomal recessive, single gene disorder (ALMS1-2p13) presenting with childhood obesity, hyperinsulinemia, type 2 diabetes mellitus, progressive cone-rod dystrophy leading to blindness, sensorineural hearing loss and function loss of multiple organs [4]. In present case report child had loss of vision, obesity, T2DM and hearing impairment from the first year of life.…”
Section: Discussionmentioning
confidence: 90%
“…Bardet-Biedl Syndrome (BBS) generally appears like AS but differs from AS in clinical features like polydactyly, brachidactyly, syndactyly, hypodontia, 50 % mental retardation and mutations of BBS gene [4].…”
Section: Discussionmentioning
confidence: 99%
“…Still, retinal dystrophy is not isolated and is accompanied with multiple organ disorders mentioned above 6,7 . Therefore, the detailed multidisciplinary approach is recommended 18 including the biological exams such as liver and kidney biological functions, search for diabetes, insulin resistance, dyslipidemia, cardiological monitoring, search for deafness and overweight care. Prenatal and predictive diagnosis should be conducted if both mutated alleles are found in the parents 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Articles whose diagnosis of ALMS was based solely on phenotype were discarded, (Charles et al, 1990; Holder et al, 1995; Russell-Eggitt et al, 1998; Koray et al, 2001; Worthley and Zeitz, 2001; Benso et al, 2002; Satman et al, 2002; Paisey et al, 2004; Hoffman et al, 2005; Hamamy et al, 2006; Koç et al, 2006; Gogi et al, 2007; Silan et al, 2013; Bronson et al, 2015; Boerwinkle et al, 2017; Davies et al, 2018), as well as those that simply presented or reported the patient’s mutations without giving an complete (Lazar et al, 2015) or individualised clinical history (Patel et al, 2006; Marshall et al, 2007b, 2015; Redin et al, 2012; Kilpinen et al, 2017; Gao et al, 2019; Baig et al, 2020). From an initial selection of 108 studies, 31 (Millay et al, 1986; Charles et al, 1990; Holder et al, 1995; Russell-Eggitt et al, 1998; Koray et al, 2001; Worthley and Zeitz, 2001; Benso et al, 2002; Satman et al, 2002; Wu et al, 2003; Iannello et al, 2004; Paisey et al, 2004; Hoffman et al, 2005; Marshall et al, 2005, 2007b, 2015; Koç et al, 2006; Patel et al, 2006; Hamamy et al, 2006; Gogi et al, 2007; Hitz et al, 2008; Catrinoiu et al, 2009; Redin et al, 2012; Silan et al, 2013; Lazar et al, 2015; Bronson et al, 2015; Ahmad et al, 2016; Huang et al, 2016; Lindsey et al, 2017; Boerwinkle et al, 2017; Gao et al, 2019; Baig et al, 2020) were discarded and 76 (Titomanlio et al, 2004; Bond et al, 2005; Minton et al, 2006; Joy et al, 2007; Özgül et al, 2007; Malm et al, 2008; Aldahmesh et al, 2009; Khoo et al, 2009; Liu et al, 2009; Kocova et al, 2011; Wang et al, 2011, 2016a, …”
Section: Methodsmentioning
confidence: 99%
“…After a thorough reading of the article, the study was included if the following characteristics were met: the cohort of the article included a patient with a diagnosis of ALMS, and the diagnosis had a genetic and clinical characterisation. Articles whose diagnosis of ALMS was based solely on phenotype were discarded, (Charles et al, 1990;Holder et al, 1995;Russell-Eggitt et al, 1998;Koray et al, 2001;Worthley and Zeitz, 2001;Benso et al, 2002;Satman et al, 2002;Paisey et al, 2004;Hoffman et al, 2005;Hamamy et al, 2006;Koç et al, 2006;Gogi et al, 2007;Silan et al, 2013;Bronson et al, 2015;Boerwinkle et al, 2017;Davies et al, 2018) , as well as those that simply presented or reported the patient's mutations without giving an complete (Lazar et al, 2015) or individualised clinical history (Patel et al, 2006;Marshall et al, 2007bMarshall et al, , 2015Redin et al, 2012;Kilpinen et al, 2017;Gao et al, 2019;Baig et al, Bea-Mascato et al, 2021;Saadah et al, 2021;Srikrupa et al, 2021;Zhang et al, 2021) were selected for information extraction and subsequent analyses.…”
Section: Study Selectionmentioning
confidence: 99%